Customer satisfaction, customer engagement, trust, and online review of maxim application user - Alfajri Wetra; Abror (Operations Management and Information System Studies, 2022)
This study's main objective was to determine how user engagement and happiness with the Maxim application in the city of Padang affected their online reviews. Second, comprehending how customer participation in online reviews is impacted by the use of the Maxim application in the city of Padang. The results of the investigation allow us to derive the following conclusions: Online Reviews (Y) of users of the Maxim application in Padang City are significantly and favorably influenced by Customer Satisfaction (X1) in that city. Online Reviews (Y) of users of the Maxim application in Padang City are positively and significantly impacted by Customer Engagement (X2) as well. Second, customer engagement (Z) users of the maxim application in Padang have a positive and considerable influence on customer satisfaction (X1) users. Third, Customer Engagement has an impact on Online Reviews through Customer Satisfaction, but Trust (X2) has a positive and significant impact on Online Reviews (Y) of users of the Maxim application in the city of Padang. Fifth, Padang's customer engagement (Z) has no bearing on online reviews (Y) of Maxim application users; if customer engagement is insignificant, then usage of the Maxim application won't increase.